2018
DOI: 10.1038/s41598-018-22797-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of combining medroxyprogesterone 17-acetate with human menopausal gonadotropin in mouse ovarian follicular development

Abstract: Medroxyprogesterone 17-acetate (MPA) combined with human menopausal gonadotropin (hMG) has been effectively used for ovarian stimulation in clinical practice. However, the molecular mechanism of MPA + hMG treatment in follicular development is poorly described. Here we performed a study to investigate the impact of MPA + hMG on ovarian stimulation utilizing a mouse model in vivo. Forty female BALB/C mice were randomly divided into four groups of 10 each and treated during ciestrus stage and continued for 5 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Cytoskeleton remodeling is one of the key factors regulating Hippo signaling and promoting the nuclear localization of YAP/TAZ complex ( 86 ). Importantly, recent findings in mouse models show that hMG administration leads to activation of the mTOR pathway ( 87 ), and GnRH induces cytoskeleton reorganization (a key process for the synthesis and secretion of gonadotropins) by activation of the mTOR kinase ( 88 ). Actin cytoskeleton dynamics mediates vital roles, also, for oocyte meiotic cell divisions through Hippo and mTOR signaling ( 89 91 ).…”
Section: The Interplay Between Pi3k/akt/mtor Axis and Hippo Pathway In Follicular Developmentmentioning
confidence: 99%
“…Cytoskeleton remodeling is one of the key factors regulating Hippo signaling and promoting the nuclear localization of YAP/TAZ complex ( 86 ). Importantly, recent findings in mouse models show that hMG administration leads to activation of the mTOR pathway ( 87 ), and GnRH induces cytoskeleton reorganization (a key process for the synthesis and secretion of gonadotropins) by activation of the mTOR kinase ( 88 ). Actin cytoskeleton dynamics mediates vital roles, also, for oocyte meiotic cell divisions through Hippo and mTOR signaling ( 89 91 ).…”
Section: The Interplay Between Pi3k/akt/mtor Axis and Hippo Pathway In Follicular Developmentmentioning
confidence: 99%
“…It has been reported that FSH, together with other paracrine factors, regulates the development of the primary follicles toward the preantral and antral stages, and a large number of LHR appear under the FSH stimulation [ 20 ]. Previous research has studied the localizations or expressions of GnRHR, FSHR and LHR in the ovaries of rats, ewes and rabbits [ 21 , 22 , 23 , 24 , 25 ]. More and more evidence showed that E 2 and ZEA induced precocious puberty in female rats by increasing the concentrations of serum FSH, LH and GnRH [ 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, maintaining the growth and development of follicles plays an important role in women's reproduction. This process is not only affected by different hormones and growth factors through endocrine, autocrine, and paracrine patterns, but also regulated by a variety of signaling pathways (Wu et al, 2012b;Fernandois et al, 2016;Hayes et al, 2016;Wen et al, 2018). The brainderived neurotrophic factor (BDNF) is one of these factors.…”
Section: Introductionmentioning
confidence: 99%